Community gardening and the capacity to enrich social bonding in urban neighborhoods - Mohd Sharif, Shahida; Ujang, Norsidah (Environmental Engineering Department, Faculty of Architecture Landscape and Environmental Technology, 2021)
This paper argues that the selection of the type of urban green spaces to be integrated into urban neighborhoods is critical in addressing these well-being problems. One of the drivers is the urban migration, where people are relocating themselves to new neighborhoods, cities or countries often with the hope of better economic opportunities and social infrastructure, therefore changing the landscape of the new society and the place they reside. It is worrying as these people might not receive enough social support due to their limited social network. It could further escalate to social well-being problems such as individualism and social isolation and could later be manifested mentally or psychologically as loneliness. Community gardens, as part of urban green spaces, offer meaningful social interaction opportunities that often being missed in the context of modern societies and urban lifestyle. Therefore, there is a need to review the effects of community gardening activities as an intervention strategy to strengthen the degree of social bonding to identify its capacity in integrating isolated people back into community life. As a conclusion, urban designers and policymakers are suggested to adopt community gardens as a safe open space in cities to encourage more people-people-places interaction.